Flotação de fosfatos presentes em minérios de ferro brasileiros - Aline Pereira Leite (2009)
Iron ore deposits are becoming increasingly complex in their mineralogical composition, as the richest ores are used up. The biggest problems are related to low levels of iron and levels of gangue are increasing. The phosphates that occur in sedimentary deposits can be primary, in the form of apatite, and secondary, forming solid solutions with oxidized iron minerals. Reducing the phosphorus content in ironores of deposits containing primary magnetite or hematite can be achieved by anionic or cationic flotation. In weathered iron ore deposits, phosphorus is highly disseminated in the form of secondary minerals. Reducing the phosphorus content is more complicated in these cases and there is no reference in the literature of studies towards theseminerals. Studies aiming at the chemical, mineralogical and morphological characterization of an iron ore sample from the Iron Ore Quadrangle of Minas Gerais,Brazil, were performed. The ore is rich, with hematite as the main ore-mineral and senegalite (an aluminium phosphate) as the main gangue mineral. Wavellite, yet anotheraluminium phosphate was also identified. The floatability of wavellite was evaluated in the presence of various fatty acids and Hidrocol was found as the best collector over the alkaline pH range. Tests with amine showed a greater than 90% recovery between pH 9.5 and pH 10.6 for wavellite. The wavellite isoelectric point was encountered at pH 4.2. The best batch flotation tests were those with starch as a depressant of iron oxides and amine EDA as collector for the phosphate phases. The best result was obtained by flotation in two stages, one with the addition of 500g/t of starch and 150g/t of amine at pH 10.5 and the second stage with the addition of 350g/t of sodium silicate and 200g/t of tall oil at pH 10.7. The product obtained in this test showed a concentrate with0.168% phosphorus from a feed grade of 0,56%P